Shear‐wave elastographic ultrasound of metacarpophalangeal synovium in rheumatoid arthritis – A pilot study. Issue 2 (2nd April 2017) - Sammel, Anthony Michael; Spies, Michael Carl; DeCarle, Rohan; Rayment, Michael; Joshua, Fredrick
Abstract: Introduction: Shear‐wave elastographic ultrasound (SW‐EUS) assesses the stiffness of human tissues. It is used in liver, thyroid and breast imaging but has not been studied in synovium. Soft tissues have a slower shear‐wave velocity (SWV) than stiff tissues. We hypothesised that rheumatoid arthritis (RA) patients would have softer synovium than controls and this could be quantified with a slower SWV. We also assessed whether SWV varied with disease activity. Methods: Nine patients with RA were consecutively recruited and matched with five controls. Participants underwent clinical assessment, blood sampling, grey scale ultrasound (GSUS), power Doppler ultrasound and SW‐EUS of MCP joints 2–5 on the dominant hand. Results: Average age was 60. Mean RA disease activity (DAS28‐ESR) was moderate at 3.65. Patients with RA had lower maximum synovial SWV than controls (6.38 m/s vs. 6.99 m/s P = 0.042). Negative Pearson's correlation coefficients (PCC) were observed between maximum SWV and disease activity markers including GSUS graded synovial thickness (PCC = −0.57, P = 0.03) and ESR (PCC = −0.46, P = 0.095). Intra‐ and interobserver reliability was good with intraclass correlation coefficients (ICC) of 0.66 and 0.58, respectively, for quantitative maximum SWV and ICC > 0.80 for colour scale rated SWV. Conclusion: This is the first pilot study of SW‐EUS in synovium. Maximum synovial SWV was significantly lower in RA than controls. There was a negative correlation between maximum SWV and GSUS synovial thickening. Further study is warranted to confirm the role of SW‐EUS in diagnosing and assessing disease activity in RA.